Enhancing speaking proficiency through retelling YouTube content for EFL learners - Suseno, Edy (Indonesian Journal of ELT and Applied Linguistics, 2023)
The most crucial aspect of learning a language is speaking. The majority of EFL students have difficulty expressing themselves. They have no idea what their speaking counter is referring to and are also at a loss for what to say. Ten college students were recruited to participate in this study which involves modifying YouTube content in improving students' speaking skills to answer this problem. First, the teacher sets up a WhatsApp group utilized to replace the classroom. Next, the teacher shared a YouTube URL with the class, instructed the students to click and learn the material, then assigned them to study the audio and text on YouTube. The students then need to retell the story after finishing the assignment. They made a recording and shared it with the group. Last, the teacher gave feedback on the students' work. The screen activities were recorded and used as the data source for qualitative analysis. As a result, the students could tell the story clearly and concisely. Their confidence to tell the story rose as well. Other teachers can use these findings to teach speaking or related disciplines, and other scholars may be able to expand on them to produce more detailed results.